2021
DOI: 10.1080/13554794.2021.1975768
|View full text |Cite
|
Sign up to set email alerts
|

A Parkinson’s disease patient displaying increased neuromelanin-sensitive areas in the substantia nigra after rehabilitation with tDCS: a case report

Abstract: Previous studies have reported that transcranial direct current stimulation (tDCS) of the frontal polar area (FPA) ameliorated motor disability in patients with Parkinson's disease (PD). Here we report changes in neuromelanin (NM) imaging of dopaminergic neurons before and after rehabilitation combined with anodal tDCS over the FPA for 2 weeks in a PD patient. After the intervention, the patient showed clinically meaningful improvements while the NM-sensitive area in the SN increased by 18.8%. This case study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…tDCS DA stimulation of the frontal pole has been reported to affect the substantia nigra and ameliorate motor deficits in PD patients [90]. Moreover, tDCS has been recently reported to affect decision-making [91] in cognitive flexibility [92,93] or attention [94], with improving effects.…”
Section: General Discussion Limitations and Conclusionmentioning
confidence: 99%
“…tDCS DA stimulation of the frontal pole has been reported to affect the substantia nigra and ameliorate motor deficits in PD patients [90]. Moreover, tDCS has been recently reported to affect decision-making [91] in cognitive flexibility [92,93] or attention [94], with improving effects.…”
Section: General Discussion Limitations and Conclusionmentioning
confidence: 99%
“…Neuromelanin can be relatively easily imaged by T1-weighted 3T-MRI [62,63]. Ishikuro et al (2021) examined effects of tDCS over the FPA in one PD patient as a case report, using noninvasive imaging of neuromelanin to reveal dopamine neurons [19]. They reported that the same tDCS protocol (i.e., 2 weeks of rehabilitation with tDCS in the FPA) increased the neuromelanin-sensitive area in the SNc, where dopamine neurons are located, from 43.2 to 53.2 mm 2 (increases by 18.8%), and that the patient exhibits clinically meaningful improvement of motor deficits (Figure 5B).…”
Section: Effects Of Tdcs Over the Fpa In Pd Patientsmentioning
confidence: 99%
“…Consistent with these findings, we will show that tDCS over the FPA is also effective in PD. Another significant issue in rehabilitation is that a substantial proportion of patients discontinue rehabilitation programs due to a loss of persistence or motivation [17][18][19]. This paper also discusses the neural mechanisms of another effect of tDCS over the FPA, especially its effect on persistence and motivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanins differ in terms of origin, color, composition, and functions they perform in organisms [1][2][3]. In humans, they are mainly known to be responsible for pigmentation of the skin, hair, and iris [4][5][6], although one type of melanin (neuromelanin) occurs in the central nervous system and does not affect pigmentation phenotype [7][8][9]. Melanins in animals are assigned a wide variety of biological functions.…”
Section: Introductionmentioning
confidence: 99%